Pengelolaan Supervisi Pendidikan Madrasah Tsanawiyah (MTs) SwastaDi Kelompok Kerja Madrasah (KKM) Tsanawiyah Kabupaten Sragen - SUKAMTA, Sukamta; , Prof. DR. Markhamah, M.Hum; , Dr. Tjipto Subadi (2017)
The objectives of the study are to describe: (1) the planning of education supervision in private Madrasah Tsanawiyah at Kelompok Kerja Madrasah (KKM) Sragen Municipality; (2) the implementation of education supervision in private Madrasah Tsanawiyah at Kelompok Kerja Madrasah (KKM) Sragen Municipality, (3) the supporting and barrier factors of education supervision in private Madrasah Tsanawiyah at Kelompok Kerja Madrasah (KKM) Sragen Municipality. The research is qualitative with fenomenology designed. Subjects of the research are madrasah principals of private Madrasah Tsanawiyah at Kelompok Kerja Madrasah (KKM) Sragen Municipality. The technique of gathering data used in this research are in depth interview, participant-observation, and documentation. The techniques of data analysis used in this research are data reduction, data display, and data verification. Data validity is checked usingmethod triangulation and source triangulation, dependability and confirmability. The results show that 1) Education supervision planning includes supervision program making at the beginning of academic year, stating objectives, preparing instruments and class visit schedules. 2) Education supervision implementation is that madrasah principals evaluate the teachers through class visit and after-class visit activities. Teachers are evaluated based on the analysis of learning administration documents and learning activities. 3) the supporting factors of education supervision are teachers' willingness to participate in sharing activities held by madrasah principals, warm relationship among teachers and between the principals and the teachers, the transparancy of financial madrasah management, supprting of the chairmen of institution and Religion Department, and good communication between madrasah and supervisors. The barrier factors include that madrasah principals do not fully understand about education supervision, time-scheduling problem and principals' business, facilities and financial problems, and there is no clear rule that principals must carry out education supervision regularly.